Copy Number Variants in Obesity-Related Syndromes: Review and Perspectives on Novel Molecular Approaches. (17th December 2012) - D'Angelo, Carla Sustek; Koiffmann, Celia Priszkulnik
Abstract : In recent decades, obesity has reached epidemic proportions worldwide and became a major concern in public health. Despite heritability estimates of 40 to 70% and the long-recognized genetic basis of obesity in a number of rare cases, the list of common obesity susceptibility variants by the currently published genome-wide association studies (GWASs) only explain a small proportion of the individual variation in risk of obesity. It was not until very recently that GWASs of copy number variants (CNVs) in individuals with extreme phenotypes reported a number of large and rare CNVs conferring high risk to obesity, and specifically deletions on chromosome 16p11.2. In this paper, we comment on the recent advances in the field of genetics of obesity with an emphasis on the genes and genomic regions implicated in highly penetrant forms of obesity associated with developmental disorders. Array genomic hybridization in this patient population has afforded discovery opportunities for CNVs that have not previously been detectable. This information can be used to generate new diagnostic arrays and sequencing platforms, which will likely enhance detection of known genetic conditions with the potential to elucidate new disease genes and ultimately help in developing a next-generation sequencing protocol relevant to clinical practice.